Galea (Rodentia, Caviidae) in the late Pleistocene of Corrientes Province (Argentina): taxonomic and paleobiogeographic implications - Francia, Analia (2012)
The Caviidae (Rodentia) are taxonomically diverse caviomorphs. Their fossil record is abundant and their oldest representatives date back to the middle/late Miocene. The genus Galea MEyEn includes small-sized species, exclusively distributed in South America. In this work we describe new remains of Galea (Rodentia, Caviidae) from the Toropí Formation (late Pleistocene, ca. 52 ka) of Corrientes Province, Argentina, and discuss the paleobiogeography of late Pleistocene species. The remains consist of a partial maxillary with complete P4-M3 dental series, anterior portion of the zygomatic arches, one associated left upper incisor, and one isolated left P4. Anatomical differences in relation to the remaining recognized species, differences in temporal and latitudinal distribution, as well as in the taxonomic composition of faunas associated to extinct species of Galea, suggest that it corresponds to a new species related to Galea tixiensis. The presence of this taxon in the late Pleistocene sediments of Corrientes Province represents a new element to characterize the complex biological dynamics of this region during much of the Pleistocene; in this area, intertropical elements co-occurred with typical Pampean-Patagonian taxa, and conditions could have eventually promoted differentiation of endemic species.